(untitled) (Research, Society and Development, 2024)
Scientific development often depends on the use of animals, but there is often a lack of awareness about ethical concepts such as animal welfare and the principles of the 3Rs (replace, reduce and improve). It is important to include other thematic content and promote debates to broaden understanding of new teaching methodologies, avoiding misinformation. Innovations in anatomy education include computer-assisted learning, virtual anatomical models, video classes, cadaver preservation techniques, among others that have been emerging to enrich the training of health professionals. Neuroimaging is a well-used resource for diagnosing CNS diseases in medicine and veterinary medicine. Sheep are used as a study model in human neuroanatomy, but research using magnetic resonance imaging (MRI) and computed tomography (CT) in sheep is still scarce. To carry out this study, the brains of 10 sheep, post-mortem, at approximately 5 months of age, were analyzed using MRI and CT images in comparison with sectional anatomy to identify neuroanatomical structures. This material was presented in class to undergraduate veterinary students as an educational dynamic. The results revealed an improvement in teaching, involving researchers and students in the use of diagnostic imaging resources, broadening students’ understanding of this area.